The Progressive Correlation Between Carbon Emission, Economic Growth, Energy Use, and Oil Consumption by the Most Prominent Contributors to Travel and Tourism GDPs - Khan, Aarif Mohammad; Basit, Asma; Khan, Uzma; Khan, Muhammad Kamran (Frontiers in Environmental Science, 2022)
Travel and tourism has glimpsed a significant and promising implication for economic development. Despite the commendatory implication of tourism, it levies a stringent environmental cost such as environmental degeneration. Hence, this study will incorporate the 18 countries out of the top 20 travel and tourism contributors to economic growth to assess the progressive correlation between tourist arrival, economic growth, energy consumption, and oil consumption on carbon emission by applying panel ARDL spanning from 1995-2019. The outcome of the panel ARDL reveals that both periods have witnessed that the endogenous variables have a substantial and positive impact on environmental degradation except for tourism, as it indicates -0.22 and -0.48 percent in the long and short-run having a rate of adjustment as -0.52 towards the equilibrium. The simultaneous quantile regression reveals that in the 50 and 75 percentile, the effect of tourism has a negative impact, which contradicts the PMG findings. These determinations suggest that the policymakers look for more manageable and environmentally sound tourism and economic growth procedures to safeguard the sustainable environment in the studied countries.